Macro-nano silver particles in-situ filled polydimethylsiloxane composites and dynamic rheological study. (November 2022) - Wu, Mingyue; Yang, Linchuan; Lei, Haijun; Zhang, Mengmeng; Zhang, Rui; Liu, Rui; Zhao, Tongtong; Xu, Xiaoyang; Guo, Yaxin; Zhu, Yuheng; Liu, Gang; Zhu, Qingzeng
Abstract: Silver-filled polydimethylsiloxanes (PDMS) are expected to be used as various advanced materials. The role of silver particles on the reinforcement and rheological behaviors of PDMS composites has not been sufficiently investigated. In addition, the processing of highly viscous PDMS mixed Ag particles is a difficult work. In this work, uniformly dispersed filled PDMS composites with macro-nano Ag were prepared by an in-situ polymerization method. The viscoelasticity and strain amplitude ( ε ) dependent rheology, also known as Payne effect, of the Ag in-situ filled PDMS composites were studied in compared with those of fumed silica-filled PDMS systems, helping to comprehend the microcosmic deformation mechanisms. Bound rubber in Ag-filled PDMS was at a low level. Ag provided a reinforcement effect and introduced a rheological nonlinearity in the PDMS composites at a critical loading of 6.10 wt%. The critical strain ( ε c = 76.5%) of vulcanized Ag-filled PDMS was insusceptible with Ag contents in the range of 3.04 wt% to 14.70 wt%. Ag and fumed silica in the composites showed different rheological behaviors. Graphical abstract: Image 1 Highlights: Macro-nano silver particle filled PDMS were prepared by an in-situ polymerization method. Bound rubbers and dynamic rheological behaviors of Ag-filled PDMS were investigated. Ag particles provide a reinforcement effect and introduce a Payne effect in PDMS. The study is of great value in engineering applications for Ag-filled PDMS.